La obra ornamental de Joaquín Orta, 1901-1915. Una lectura iconográfica de tres espacios religiosos en Tlalpujahua y Morelia, Michoacán - Medrano Pantoja, Nadia Andrea (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
The Romantic ideas of the 19th century during the Porfirian period in Mexico influenced the phytomorphic plastic manifestation of Joaquín Orta's ornamental work in the religious architecture of Michoacán during the first two decades of the 20th century. The decorations he developed (1901-1915) in the interiors of the Sanctuary of Our Lady of Guadalupe in the city of Morelia, the Sanctuary of the Virgin of Carmen, and the Temple of the Virgin of Guadalupe in the Franciscan convent in the municipality of Tlalpujahua, are a metaphorical reflection of elements from nature and the Marian invocations of the temples he worked on. Joaquín Orta Menchaca was born in Tlalpujahua, Michoacán, a municipality where he worked in the fields of mechanics and watchmaking. This research addresses the question: What iconographic elements characterize the work of Joaquín Orta, and what processes led to the execution of this ornamentation in three religious’ spaces? The objective was to explain the characteristics of Joaquín Orta's work through an iconographic reading, with the expectation that the results of this study could serve methodologically for the analysis of other case studies. The methodology designed is divided into historical research and iconographic analysis, based on the approaches of Erwin Panofsky and González de Zárate. The research instruments used helped in the historical and historiographical reconstruction of the figure and the iconographic reading of the religious interiors.

Las ideas romanticistas del siglo XIX en el periodo porfirista de México influyeron en la manifestación plástica fitomorfa de la obra ornamental de Joaquín Orta en la arquitectura religiosa de Michoacán durante las primeras dos décadas del siglo XX. Los decorados que desarrolló (1901-1915) en los interiores del Santuario de Nuestra Señora de Guadalupe en la ciudad de Morelia, el Santuario de la Virgen del Carmen y el templo de la Virgen de Guadalupe del convento franciscano en el municipio de Tlalpujahua, son reflejo metafórico hacia los elementos de la naturaleza y las advocaciones marianas de los templos que intervino. Joaquín Orta Menchaca nació en Tlalpujahua, Michoacán, municipio en el que desempeñaba el oficio de la mecánica y la relojería. Esta investigación responde a la pregunta sobre ¿Qué elementos iconográficos caracterizan la obra de Joaquín Orta, y cuáles fueron los procesos que dieron pie a que se ejecutara esta ornamentación en tres espacios religiosos? Como objetivo, se buscó explicar las características del trabajo de Joaquín Orta desde una lectura iconográfica donde se espera que el resultado de este trabajo pueda funcionar metodológicamente para el análisis de otros casos de estudio. La metodología que se diseñó se divide en la cuestión histórica y el análisis iconográfico por parte de Erwin Panofsky y González de Zarate. Con apoyo de instrumentos de investigación que se utilizaron para la reconstrucción histórica e historiográfica del personaje y la lectura iconográfica ornamental de los interiores religiosos.
Facultad de Arquitectura. Maestría en Arquitectura y Patrimonio Cultural
Keywords: info:eu-repo/classification/cti/4; FA-M-2024-1867; Iconografía; Eclecticismo; Arquitectura religiosa; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18962